1997
DOI: 10.1093/chemse/22.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Odor Hedonics: Connection With Emotional Response Estimated by Autonomic Parameters

Abstract: The aim of this paper is to analyse the relationship between self-report hedonic evaluations and the physiological expression of emotion in response to odorants. We try to solve the following questions: (1) Is it possible to find any experimental evidence that the sense of smell is linked with emotion? (2) What kind of odorants can be distinguished by autonomic analysis? (3) Is there a link between hedonics and autonomic information? The effects of odorants on the emotional process were estimated, in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
95
1
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(113 citation statements)
references
References 40 publications
9
95
1
4
Order By: Relevance
“…Previously, two research teams demonstrated that an increase in HR variation typically accompanies an unpleasant odorant inhaling experience (Alaoui-Ismaïli et al, 1997b;Bensafi et al, 2002aBensafi et al, , 2002b. Our findings suggest that the implicit objective measures support the same negative "bias" as the subjective explicit responses.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Previously, two research teams demonstrated that an increase in HR variation typically accompanies an unpleasant odorant inhaling experience (Alaoui-Ismaïli et al, 1997b;Bensafi et al, 2002aBensafi et al, , 2002b. Our findings suggest that the implicit objective measures support the same negative "bias" as the subjective explicit responses.…”
Section: Discussionsupporting
confidence: 61%
“…To our knowledge, only one study has used an objective measure (eventrelated potential analysis) to investigate the emotional response to odour in depression (Pause et al, 2003). Furthermore, no research has studied the physiological reactivity to odour in depression, while it has been demonstrated that variations in electrodermal (skin conductance, skin resistance), thermovascular (skin blood flow) and cardiorespiratory (instantaneous heart rate) responses could be modulated by odour pleasantness (Alaoui-Ismaïli et al, 1997a, 1997bVernet-Maury et al, 1999;Bensafi et al, 2002a). For instance, it has been shown that decreases in instantaneous HR variation are associated with pleasant odours, while increases in HR variation are associated with unpleasant odours.…”
Section: Objective Evaluation Of the Olfactory Hedonic Responsementioning
confidence: 99%
“…The increase of alpha 2 activity during late exposure (120-150 s) to incense suggests that the odor of incense affects not only the primary olfactory cortex, but also the adjoining cortices. The primary olfactory cortex is connected with the limbic cortex, hypothalamus, hip- pocampus, insular cortex, and orbitofrontal cortex, which are related to emotion and memories [23,24] . Therefore, it is possible that the odor of incense may induce strong emotional responses and memories.…”
Section: Discussionmentioning
confidence: 99%
“…One is pharmacological, via direct interactions between odor molecules and receptors or nerve endings, and the other is psychological via the subjective experience of odors (Alaoui-Ismaili et al 1997;Heuberger et al 2001;Jellinek 1997). Our results suggest that the principal odor component of jasmine tea, especially, (R)-())-linalool, exerts a pharmacological sedative effect.…”
Section: Discussionmentioning
confidence: 99%